ANALYSIS OF DETERMINATION OF POSITION BASED ON CONTRIBUTION OF TASK AND WORK ACHIEVEMENT - Munir, Misbahul; Erdianto, Yoniv; Suparto, Suparto; Suparjo, Suparjo (Institut Teknologi Adhi Tama Surabaya, 2021)
To find the value of employee achievement requires several aspects such as intelligence, aspects of work attitudes, and behavioral. The initial stage of the process is to find the difference between employee and position profile that has been determined by the company where it is called GAP. The next step is to determine the weight of each gap value in three aspects. We multiply the value of 60% for the value of the main factor and 40% for additional factors then add up the two factors to determine the total value. The three factors are assessed based on the percentage determined by the company, namely 25% Intelligence Aspect, 35% Behavioral Aspect, and 40% Work Attitude Aspect. The final results are ranked, and then top ranking is achieved until the last employees who occupy the position of Project Supervisor are employees with ID number: kka_0001. For employees who are likely to fill the position of Purchasing & Logistics are employees with ID number: kka_0040. For employees who are likely to occupy the Estimator position are employees with ID number: kka_0036. For employees who fill the Project Manager position are employees with ID number: kka_0055.